Analisis Estetika Warna Sebagai Komunikasi Visual Dalam Anime Kimetsu No Yaiba: Mugen Train - Anggraini, Novitri; Kurnia SF, Aka (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Color is an important element of visual communication that functions not only as an aesthetic component but also as a medium for conveying messages, creating atmosphere, and evoking emotional responses from audiences. This study aims to analyze the use of color as a form of visual communication in the movie Kimetsu no Yaiba: Mugen Train and to examine its role in shaping mood and audience emotions. The research employs a qualitative interpretive approach with a descriptive research design. Data were collected through visual observation, documentation, and literature review, and were analyzed using Donis A. Dondis’s visual communication theory and Johann Wolfgang von Goethe’s color theory. The findings indicate that color functions as a visual communication medium capable of conveying meaning nonverbally. Warm colors such as red, orange, and yellow are used to create dynamic, energetic, and tense atmospheres, while cool colors such as blue, green, and purple are employed to evoke calm, reflective, and emotional moods. Through the combination of color, lighting, and visual composition, the film strengthens its narrative, represents the emotional states of characters, and enhances audience engagement. Therefore, color serves not merely as a visual element but also as a significant component of visual communication that contributes to the construction of meaning, atmosphere, and emotion within the film.